1983
DOI: 10.1128/jcm.18.5.1275-1277.1983
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of enterococci

Abstract: A 4-h method was devised to differentiate the non-beta-hemolytic streptococci into three categories: enterococci, group D nonenterococci, and viridans streptococci. All of the Streptococcus faecalis, 90% of the Streptococcus faecium (enterococci), and 96% of the Streptococcus bovis biotype I (group D nonenterococci) cultures were correctly identified by the 4-h method. The less commonly isolated group D cultures had lower rates of correct identification by this method. None of the viridans streptococci was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
4

Year Published

1984
1984
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 6 publications
0
15
0
4
Order By: Relevance
“…The data obtained with the disks containing C. perfringens alpha-toxin are not shown, but the reactions of the reference and clinical strains tested with the C. perfringens alpha-toxin were identical to those seen with the beta-lysin of S. intermedius except for two species; all strains of S. hyicus and S. chromogenes were negative by this method. Many of the positive strains produced clear zones after only 2 h, and all reactions were complete within 4 h.…”
Section: Resultsmentioning
confidence: 95%
“…The data obtained with the disks containing C. perfringens alpha-toxin are not shown, but the reactions of the reference and clinical strains tested with the C. perfringens alpha-toxin were identical to those seen with the beta-lysin of S. intermedius except for two species; all strains of S. hyicus and S. chromogenes were negative by this method. Many of the positive strains produced clear zones after only 2 h, and all reactions were complete within 4 h.…”
Section: Resultsmentioning
confidence: 95%
“…,[171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186] Because PYRase has a specific enzymatic activity, chromogenic and fluorogenic substrates have been developed to differentiate bacteria based on PYRase activity. Such substrates included: The identification of bacteria based on PYRase activity can also be performed in liquid culture and on agar media.lE7 In addition, tests have been developed for direct bacterial identification from clinical human and animal samples.181~1s2~188 It is worth noting that the PYRase test alone may not be sufficient for bacterial (pathogen) identification when applied to clinical samples, and thus this test is usually accompanied by other enzymatic tests and serological tests for confirmation.…”
mentioning
confidence: 99%
“…For the present study, we received 42 Sharpe's serotype strains from NIRD, and we first examined for their biochemical characteristics of E. faecalis in Api STREP 20 kit as recommended by several investigators (1,2,13), because the characteristics of these strains as E. faecalis have not been determined since they were deposited in NIRD and NCTC. We found that only 9 strains of the 42 strains were identified as E. faecalis, and that even 23 strains deposited in NCTC as Sharpe's serotypes 1-16, 18-24 (corresponding to Group D Sharpe and Shattock serotypes NCTC 8727, 8796, 8729-8749 in the catalogues of the National Collections of Type Cultures and Pathogenic Fungi, 1989) included strains of 4 different species of genus Enterococcus and strains of genus Streptococcus.…”
Section: Discussionmentioning
confidence: 99%